Perencanaan Rumah Minimalis Ramah Lingkungan di Kelurahan Poris Plawad Utara, Cipondoh, Tangerang, Banten - Abdillah, Hafiz (Universitas Batanghari Jambi, 2024)
Poris Plawad Utara, Cipondoh, Tangerang, Banten is a densely populated area, this is due to the large number of incomers who live or reside there. Due to those conditions, there is a must to educate the residents to have plan in designing the healthy and environmentally friendly home. It needs to pay an attention for aspects of the surrounding environmental conditions in planning a healthy and environmentally friendly residence, such as circulation of the sun, wind movement, availability of open areas and other environmental aspects to meet residential needs for thermal comfort. To achieve these ideal conditions, it is a necessary to pay an attention to the natural ventilation circulation system and natural lighting. From the results of the research carried out, it can be concluded that the ideal building orientation is facing east-west, in this direction, the sunlight shines throughout the day. If the light intensity is high, vegetation can be planted in the area around the building with shady and cooling tree species, it can also provide alternatives to the building structure such as making wooden slats in the direction of the sun to reduce glare and maximize openings to circulate air from outside the room. To provide natural coolness to the building, distance is created in between each the building so that the wind can move freely in the room.